2021
DOI: 10.1186/s13104-021-05706-5
|View full text |Cite
|
Sign up to set email alerts
|

Gut micobiota alteration by Lactobacillus rhamnosus reduces pro-inflammatory cytokines and glucose level in the adult model of Zebrafish

Abstract: Objective Type 2 diabetes mellitus (T2DM) is still a challenge for physicians to manage patient’s circumstances. It is assumed that alterations in the normal flora may be involved in the pathogenesis of T2DM through inducing chronic inflammation. To investigate the effect of Lactobacillus rhamnosus as a common probiotic on T2DM, we induced an experimental model of T2DM in adult male Zebrafish by gradient hyper-glucose accumulation methodology. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The mechanisms by which Lactobacillus supplementation may have beneficial effects on glycemic control, the lipid profile, and blood pressure have yet to be fully elucidated. First, a study by Bootorabi et al demonstrated that Lactobacillus rhamnosus reduces blood glucose by reducing the concentrations of pro-inflammatory cytokines that contribute to the pathogenesis of T2DM [49]. Another study by Wu et al showed that L. rhamnosus reduces FPG and insulin resistance via effects on the glucagon signaling pathway and the gut microbiota [50].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which Lactobacillus supplementation may have beneficial effects on glycemic control, the lipid profile, and blood pressure have yet to be fully elucidated. First, a study by Bootorabi et al demonstrated that Lactobacillus rhamnosus reduces blood glucose by reducing the concentrations of pro-inflammatory cytokines that contribute to the pathogenesis of T2DM [49]. Another study by Wu et al showed that L. rhamnosus reduces FPG and insulin resistance via effects on the glucagon signaling pathway and the gut microbiota [50].…”
Section: Discussionmentioning
confidence: 99%
“… 62 Furthermore, Bootorab et al found that blood glucose levels were decreased after probiotic L. rhamnosus administration via downregulation of proinflammatory cytokines (such as TNF‐α and IL‐1β) involved in T2DM therapeutic signaling pathways. 63 Importantly, it has been found that Escherichia coli could utilize glucose and produce acidic byproducts of glucose metabolism in the zebrafish gut. These acidic products significantly reduced the colonization rate of the classical and EI Tor biotypes of V. cholerae to prevent or treat cholera infection.…”
Section: The Roles Of the Gut Microbiome In Tissue Development And Ph...mentioning
confidence: 99%
“…In addition, the α‐diversity (the Chao1 index) was decreased in T2DM adult zebrafish compared with the healthy controls 62 . Furthermore, Bootorab et al found that blood glucose levels were decreased after probiotic L. rhamnosus administration via downregulation of proinflammatory cytokines (such as TNF‐α and IL‐1β) involved in T2DM therapeutic signaling pathways 63 . Importantly, it has been found that Escherichia coli could utilize glucose and produce acidic byproducts of glucose metabolism in the zebrafish gut.…”
Section: The Roles Of the Gut Microbiome In Tissue Development And Ph...mentioning
confidence: 99%
“…rhamnosus on Type 2 diabetes mellitus (T2DM) was investigated in T2DM-induced adult male zebrafish. The results revealed that probiotic administration decreased the blood glucose level by decreasing pro-inflammatory cytokines responsible for signaling in T2DM [ 72 ].…”
Section: Probiotics and Metabolismmentioning
confidence: 99%